Changes in China's production-source CO2 emissions: insights from structural decomposition analysis and linkage analysis. Issue 2 (2nd April 2016) - Chang, Ning; Lahr, Michael L.
ABSTRACT: This paper presents an input–output based methodology – structural decomposition analysis (SDA) plus linkage analysis, for identifying the key factors and sectors that affected production-source CO2 emissions in China. The proposed methodology extends the SDA to account for the import substitution effect within an open economy such as China and incorporates the emission linkage by which the effect of the input mix on CO2 emissions can be understood in depth. Empirical results indicate that, between 2005 and 2010, improving emission intensity and input intensity had helped to reduce CO2 emissions; meanwhile, capital investment explained the majority of the increases in CO2 emissions brought about by final demand, and import substitution was also observed to increase CO2 emissions. Moreover, nine key emission sectors have been identified, and in this regard, domestic inputs became more CO2 -intensive in 2010 than it was in 2005.